Workplace genetic testing: which employees are likely to participate, what are their concerns with employer sponsorship, and which design features could reduce barriers and increase participation? - Briscoe, Forrest; Maxwell, James H.; Bourgoin, Angel (Frontiers in Genetics, 2024)
Voluntary genetic testing (GT) leverages low-cost DNA sequencing and other testing methods to provide genetic risk screening for healthy individuals. Given the potential to prevent disease and promote health, some employers now offer GT as an employee benefit (workplace GT, or wGT), but participation remains low. To investigate facilitators and barriers to wGT participation, we conducted one of the first representative surveys of working U.S. adults on this topic (n = 958). We assessed factors that could influence participation, including: sponsoring entity (health provider or employer), program design, and individual demographics. Two-thirds (68%) of respondents indicated willingness to participate in some type of GT, but only half (49%) expressed willingness to participate through their employer. Women were 60% more willing to participate than men, and individuals with previous genetic testing experience were 143% more willing to participate than those without such experience. Across all demographic groups, certain GT program design features tended to increase or decrease willingness to participate. The ability to have one’s data deleted from the GT database increased willingness most often (true for 67% of respondents), while selling data to pharmaceutical companies decreased willingness most often (true for 63% of respondents).